The future excess fraction of cancer due to lifestyle factors in Australia - Carey, Renee; Whiteman, D.C.; Webb, P.M.; Neale, R.E.; Reid, Alison; Norman, Richard; Fritschi, Lin (ELSEVIER SCI LTD, 2021)
Background: Many cancers are caused by exposure to lifestyle, environmental, and occupational factors. Earlier studies have estimated the number of cancers occurring in a single year which are attributable to past exposures to these factors. However, there is now increasing appreciation that estimates of the future burden of cancer may be more useful for policy and prevention. We aimed to calculate the future number of cancers expected to arise as a result of exposure to 23 modifiable risk factors. Methods: We used the future excess fraction (FEF) method to estimate the lifetime burden of cancer (2016–2098) among Australian adults who were exposed to modifiable lifestyle, environmental, and occupational risk factors in 2016. Calculations were conducted for 26 cancer sites and 78 cancer-risk factor pairings. Results: The cohort of 18.8 million adult Australians in 2016 will develop an estimated 7.6 million cancers during their lifetime, of which 1.8 million (24%) will be attributable to exposure to modifiable risk factors. Cancer sites with the highest number of future attributable cancers were colon and rectum (n = 717,700), lung (n = 380,400), and liver (n = 103,200). The highest number of future cancers will be attributable to exposure to tobacco smoke (n = 583,500), followed by overweight/obesity (n = 333,100) and alcohol consumption (n = 249,700). Conclusion: A significant proportion of future cancers will result from recent levels of exposure to modifiable risk factors. Our results provide direct, pertinent information to help determine where preventive measures could best be targeted.